An Assessment of Vitamin B12 Deficiency in Infants under Six Months with Severe Acute Malnutrition - Dr. Lipi Roat; Dr. R.L. Suman; Dr. Mukesh Kumar Jat, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background - NFHS-5 shows improved nutrition indicators for children under 5, with lower rates of stunting, wasting, and underweight. However, interventions primarily target older children, neglecting the high prevalence of infant malnutrition. Vitamin B12 deficiency during infancy can cause anemia, poor growth, neurological damage, and developmental delays. Methodology - This prospective observational study was conducted at Balchikitsalaya from June 2021 to December 2022. It includes 100 infants under 6 months with severe acute malnutrition, and data on demographics, clinical features, and vitamin B12 levels were collected. Descriptive statistics and statistical tests were used to analyze the data and assess the prevalence of vitamin B12 deficiency and its association with clinical features. Result – Maximum number of infants with vitamin B12 deficiency were in age of 5-6 month. Loose stool and vomiting were the most common complaints. Low vitamin B12 level was found in 48% of infants. Clinical manifestations such as pallor, hyperpigmentation, and tremor were significantly associated with Vitamin B12 deficiency. There was significant association between vitamin B12 deficiency and anemia (p<0.001) and, thrombocytopenia (p<0.001). 29 infants had tremor, out of them 25 patients had vitamin B12 deficiency. This study shows significant association between tremor and low vitamin B12 deficiency (P<0.001). There was significant association between BMI and vitamin B12 level in mother (P=0.012). Conclusion: Prevalence of vitamin B12 deficiency in less than six months infants with SAM was 48 % and tremors have significant association (p:001).